Efektivitas Mediasi sebagai Alternatif Penyelesaian Sengketa Wanprestasi dalam Perjanjian Kredit: Studi pada Lembaga Bantuan Hukum Surya NTT - Ansgeryan Risaldi Triputra Oman; Yossie Maria Y. Jacob; Rini Marselin Kaesmetan (Student Research Journal, 2026)
This study examines the effectiveness of mediation as an alternative dispute resolution method for breach of contract disputes in credit agreements at Lembaga Bantuan Hukum Surya NTT. The research used an empirical juridical approach with descriptive qualitative methods. Data were obtained through interviews, documentation, and literature study involving legal aid advocates and clients involved in credit agreement disputes. The results show that mediation is relatively effective because it provides faster, less expensive, and more flexible dispute resolution compared to litigation. Mediation also encourages communication between parties and helps achieve mutually acceptable agreements. However, its effectiveness is still influenced by good faith, legal awareness, and the economic conditions of the parties involved. The implementation of rights and obligations after mediation generally runs well, although delays in fulfilling obligations are still found in several cases.